Toward a Conceptual Framework for the Study of Folklore and the Internet - Blank, Trevor J. (Current arguments in folklore., 2014)
Trevor J. Blank broke new ground for the field of folklore studies in this essay by rationalizing the study of the internet as an important area of expressive vernacular culture. Pushing back against traditionalists who dismissed the digital as simply the domain of technicians and mass media, Blank argues that "from the earliest moments of the modern Internet's existence, folklore was a central component of the domain, moderating the intersection of computer professionals with hackers, newfangled lingo, and the dispersal of stories, pranks, and legends." With this essay and the volume it introduces, Blank theorizes the internet as an important analytic venue for folklorists, and sets the agenda for digital folklore research.